2013
DOI: 10.1149/04601.0229ecst
|View full text |Cite
|
Sign up to set email alerts
|

Knudsen Effusion Mass Spectrometric Study of Some Congruently and Incongruently Vaporizing Systems

Abstract: We have performed KEMS measurements on both congruently and incongruently vaporizing systems. The congruently vaporizing compounds include TeO2(s), MnTe(s), H3BO3(s), and NaBO2(s). The incongruently vaporizing systems include binary tellurides of Fe, Cr, Ni, Mo, Mn, and the ternary Mn-Te-O. The various aspects concerning the vaporization behavior of these systems will be presented in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Vaporization thermodynamic studies on tellurium and its compounds with oxygen or clad components are of great importance in understanding the fuel-clad chemical interactions in nuclear technology. A summary of our earlier studies on M-Te and MnTe-O systems have been described in our recent publications and the references quoted therein [2,3]. During these studies, apart from generating phase diagram and thermodynamic data, we observed interesting vaporization behavior of condensed phases [4,5].…”
Section: Introductionmentioning
confidence: 79%
“…Vaporization thermodynamic studies on tellurium and its compounds with oxygen or clad components are of great importance in understanding the fuel-clad chemical interactions in nuclear technology. A summary of our earlier studies on M-Te and MnTe-O systems have been described in our recent publications and the references quoted therein [2,3]. During these studies, apart from generating phase diagram and thermodynamic data, we observed interesting vaporization behavior of condensed phases [4,5].…”
Section: Introductionmentioning
confidence: 79%